Postweaning Consumption of Aqueous Extract of Hibiscus sabdariffa May Predispose Rats to Obesity - Iyare, E.E.; Nwagha, U.I. (Pakistan Journal of Nutrition, 2009)
This study investigated whether consumption of aqueous extract of Hibiscus sabdariffa during the juvenile-pubertal period will affect the BMI and visceral organ weights at onset of puberty in rats. Weaned 21 days old rats, whose mothers were given food and water ad libitum during pregnancy and lactation, were divided randomly into three groups of nine rats each. Control group had tap water only while the extract groups had 0.6 g-extract/100 ml and 1.8 g-extract/100 ml as their drinking solution throughout the juvenile-pubertal period (PND 21-puberty onset). All groups had normal rat chow and their respective drinking solutions ad libitum. From PND 30 onwards, the rats were inspected daily for vaginal opening, which was used as the index for puberty onset. Rats in the extract groups (0.6 g/100 ml and 1.8 g/100 ml) drank less fluid and consumed less food compared with the control group at all periods of measurement. The weight of 0.6 g/100 ml was not different from the control whereas 1.8 g/100 ml was lower at PND 28, similar at PND 35 and higher at PND 42 and at puberty onset compared with the control. Puberty onset in the extract groups was delayed and body weights and lengths, BMI, visceral organs weights and weight indices were higher in the extract groups. It is concluded that consumption of aqueous extract of Hibiscus sabdariffa during the juvenile-pubertal period decreased fluid and food consumption, increased BMI and visceral organs’ weights and may predispose to obesity at puberty onset in rats.